Dampak African Swine Fever terhadap Aspek Finansial Peternakan Babi di Kabupaten Toba Sumatera Utara - G. Sipayung; L. Cyrilla; S. Sinaga (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2022)
Pigs are one of the livestock commodities that have the potential to be developed. There was a markedly decreased pig population in Toba Regency due to African Swine Fever (ASF) outbreak in 2019. This study aims to analyze the economic impact of ASF outbreaks on the financial of pig farming in Toba Regency. The research was conducted on a small-scale farm at Toba Regency North Sumatera. Data collection was carried out from May-July 2022 by interviewing 60 pig farmers. The impact of ASF on the financial of pig farming was measured by income analysis, Revenue Cost Ratio (R/C), and Benefit Cost Ratio (B/C). The results showed that the financial of pig farming at Kabupaten Toba with 10 sows the income, Revenue Cost Ratio (R/C), Benefit Cost Ratio (B/C); Rp 9.462.617,38; 1.2 and 0.2 before ASF and increased to Rp 55.434.480,13; R/C 2 and B/C 1 post ASF.